Concerns About Patient Safety Related to Electronic Health Records: Scale Development - Aya Al-Ali; Laila Akhu-Zaheya; Salam Bani Hani (Quality Management in Health Care, 2026)
Background and Objectives: Electronic health record (EHR) implementation impacted patient safety since it has the potential to increase the standard and safety of medical care. This study aims to develop a scale for measuring EHR-related patient safety concerns and investigates differences in hospitals and participants in terms of these safety concerns. Methods: Nonexperimental, methodological design was used in this study. A mixed approach was used, including a qualitative focus group interview and a quantitative survey. Results: Five factors were retained, and they suggested 5 factors: clinical communication, EHR alert system, patient identification, the most recent data usage, and clinical documentation. The total number of participants who completed the questionnaires was 602 nurses and midwives, with a 67% response rate. Conclusion: Administrations are committed to creating a safety culture among users of EHR, and continuous evaluation and assessment of skills and competencies has of great impact on patient safety.